If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 4 + 3x + -6 = 8x + 4 Reorder the terms: 4 + -6 + 3x + 3x = 8x + 4 Combine like terms: 4 + -6 = -2 -2 + 3x + 3x = 8x + 4 Combine like terms: 3x + 3x = 6x -2 + 6x = 8x + 4 Reorder the terms: -2 + 6x = 4 + 8x Solving -2 + 6x = 4 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -2 + 6x + -8x = 4 + 8x + -8x Combine like terms: 6x + -8x = -2x -2 + -2x = 4 + 8x + -8x Combine like terms: 8x + -8x = 0 -2 + -2x = 4 + 0 -2 + -2x = 4 Add '2' to each side of the equation. -2 + 2 + -2x = 4 + 2 Combine like terms: -2 + 2 = 0 0 + -2x = 4 + 2 -2x = 4 + 2 Combine like terms: 4 + 2 = 6 -2x = 6 Divide each side by '-2'. x = -3 Simplifying x = -3
| -14=-6+4e | | 29=-x+7x-1 | | 3x+5+3x-6=10x-2 | | 2=1.2+-0.2y | | 30x+5=64 | | 1=1.2+-0.2y | | 42x^2-480x-2463=0 | | 120+.30x=80+.50x | | x+2y-1=6x-9 | | -4m+13=9 | | 3+6cosx=0 | | u^2+u-21=0 | | -6m-13=163 | | 6+0.4x=18+.02 | | 4(-2m-5)+8m=-15 | | 287+49m+7n=-64+4m-2n | | 322-(-159)+10-159+78= | | 39x^2-482x-2464=0 | | X+(x+3)=61 | | 2x-4=3x+12 | | .06+.04x=18+.02 | | 8(b+7)=0 | | y=-4*-4+2*-4-7 | | 36y^7+4y^4= | | 4.5/g+2=3/0.5g-1 | | 12-5+x=5+8-2 | | 8x+2y+2=180 | | (2x+7)=87 | | 5d-4(d-9)=3d-(9-d) | | 3.5t+8=2.25t-16 | | 0.92x+.98(12-x)=.96(12) | | 3x^2-12x+165=180 |